Signal transduction pathway of TonB-dependent transporters - Ferguson, Andrew D. (National Academy of Sciences, 2007)
Transcription of the ferric citrate import system is regulated by ferric citrate binding to the outer membrane transporter FecA. A signal indicating transporter occupancy is relayed across the outer membrane to energy-transducing and regulatory proteins embedded in the cytoplasmic membrane. Because transcriptional activation is not coupled to ferric citrate import, an allosteric mechanism underlies this complex signaling mechanism. Using evolution-based statistical analysis we have identified a sparse but structurally connected network of residues that links distant functional sites in FecA. Functional analyses of these positions confirm their involvement in the mechanism that regulates transcriptional activation in response to ferric citrate binding at the cell surface. This mechanism appears to be conserved and provides the structural basis for the allosteric signaling of TonB-dependent transporters.